Meditation buffers medical student compassion from the deleterious effects of depression. Issue 2 (4th March 2018) - Mascaro, Jennifer S.; Kelley, Sean; Darcher, Alana; Negi, Lobsang Tenzin; Worthman, Carol; Miller, Andrew; Raison, Charles
Abstract: Increasing data suggest that for medical school students the stress of academic and psychological demands can impair social emotions that are a core aspect of compassion and ultimately physician competence. Few interventions have proven successful for enhancing physician compassion in ways that persist in the face of suffering and that enable sustained caretaker well-being. To address this issue, the current study was designed to (1) investigate the feasibility of cognitively-based compassion training (CBCT) for second-year medical students, and (2) test whether CBCT decreases depression, enhances compassion, and improves daily functioning in medical students. Compared to the wait-list group, students randomized to CBCT reported increased compassion, and decreased loneliness and depression. Changes in compassion were most robust in individuals reporting high levels of depression at baseline, suggesting that CBCT may benefit those most in need by breaking the link between personal suffering and a concomitant drop in compassion.